Behaviour of two spans continuous steel fibre reinforced concrete beam under monotonic loading - Heng, Renyi (2014)
The experimental work presented herein is aimed at studying the effect of steel fibres on the behaviour of reinforced concrete (RC) structures designed accordance with Eurocode 2. An attempt has been made to investigate the potential use of steel fibres can result in a significant reduction in conventional shear reinforcement and satisfied the requirement of current codes for strength and ductility. In this respect, hooked end steel fibres with aspect ratio .of 80 were used. Three different dosages of steel fibres in the concrete mix was based on the volume fraction of 0, 1 and 2% (0, 82, 164 kg/m'). In this particular case, additional reduction of the conventional shear reinforcement was carried out by spacing increases (SI) of the stirrups by 50% to see whether the loss of shear strength can be compensated by addition of steel fibre. Concrete compression and flexural tests were conducted for studying the compressive, strength, load-carrying capacity, ductility and energy absorption. In order to determine its mechanical properties, 27 cubes of all sides equal to 100 mm and 6 beams of dimension 200x200x3000mm were casted. All cubes specimens was tested until failure in compression machine and found out that the compressive strength of steel fibre reinforced concrete (SFRC) is not influenced by the steel fibre contribution. However, in the flexural test of beam specimens under monotonic loading; the results indicate steel fibre highly enhanced the flexural strength of SFRC beam. Conclusively, the results revealed that steel fibres give insignificant effect to the compressive strength but highly contribute to strength enhancement of SFRC flexural behaviour. Inclusion of steel fibres allowed for a reduction of conventional shear reinforcement without compromising the ductility and load-carrying capacity. This effect has extended the mode of failure of the beam changed from brittle to a more ductile manner as the amount of steel fibres was increased in the concrete mix.